The Angiosome Concept Evaluated on the Basis of Microperfusion in Critical Limb Ischemia Patients-an Oxygen to See Guided Study - Rother, Ulrich; Kapust, Johannes; Lang, Werner; Horch, Raymund E.; Gefeller, Olaf; Meyer, Alexander (Microcirculation, 2015)
Aim of this clinical study was to evaluate the angiosome concept with regard to the microcirculation of the foot in patients with CLI and to evaluate its relevance by means of combined laser Doppler flowmetrie and white-light tissue spectrophotometry.Twenty-eight patients who underwent leg revascularization in the stage of CLI were prospectively examined. The microperfusion was assessed by light guided spectrophotometry. The measuring points were set according to the angiosome concept into direct and indirect revascularized areas of the foot. Investigations were performed pre and postinterventionally and after 4 and 12 weeks in baseline-position as well as in an elevated position of the leg.Microcirculation parameters (oxygen saturation, blood flow, velocity) of the revascularized leg showed a significant increase in elevation and baseline position compared to the preoperative values in most analyses. No significant differences between the direct and indirect revascularized angiosome were apparent.The light-guided spectrophotometry measurement proved to be feasible in terms of measuring changes in the microcirculation after leg revascularization. However, our data do not support the value of the "angiosome concept" concerning the individual changes in microperfusion of the foot in patients with CLI.
EVALuna2:5490